Coexistence of allergic bronchopulmonary aspergillosis and allergic aspergillus sinusitis in a patient without clinical asthma. (2nd May 2013) - Ghosh, Gopal; Sharma, Brijesh; Chauhan, Ajay; Chawla, M P S
Abstract : All patients with prolonged cough with a history of atopy, even if not clinically asthmatic, should be evaluated for allergic bronchopulmonary aspergillosis (ABPA); also, we suspect that we may miss the early diagnosis of ABPA if bronchial asthma is considered as a major criteria for the diagnosis of ABPA